2015
DOI: 10.1021/la504672x
|View full text |Cite
|
Sign up to set email alerts
|

Templated Self-Assembly of Block Copolymers and Morphology Transformation Driven by the Rayleigh Instability

Abstract: In the current study, we investigate the self-assembly of polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) confined in the nanopores of the anodic aluminum oxide (AAO) template and the subsequent morphology transformation induced by the Rayleigh instability. PS-b-P4VP nanotubes and nanorods with various internal nanostructures are fabricated by wetting the AAO template with PS-b-P4VP/chloroform solution, and then followed by solvent evaporation. After the removal of AAO template by potassium hydroxide solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…An important contribution from the mean curvature to the microstructural evolution in polymer solutions is shown in a recent work of Yan et al [73] In this work, it is found that a polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) nanorod decomposes into several polymer-particles. An important contribution from the mean curvature to the microstructural evolution in polymer solutions is shown in a recent work of Yan et al [73] In this work, it is found that a polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) nanorod decomposes into several polymer-particles.…”
Section: Hydrodynamic Effectsmentioning
confidence: 66%
See 1 more Smart Citation
“…An important contribution from the mean curvature to the microstructural evolution in polymer solutions is shown in a recent work of Yan et al [73] In this work, it is found that a polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) nanorod decomposes into several polymer-particles. An important contribution from the mean curvature to the microstructural evolution in polymer solutions is shown in a recent work of Yan et al [73] In this work, it is found that a polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) nanorod decomposes into several polymer-particles.…”
Section: Hydrodynamic Effectsmentioning
confidence: 66%
“…[43] Copyright 2018, American Chemical Society. [73] Copyright 2015, American Chemical Society. Reproduced with permission.…”
Section: Hydrodynamic Effectsmentioning
confidence: 99%
“…At the later stage, the cylinder breaks into spheres with an average diameter d = 3.78 R 0 . Not only for simple liquids, the Rayleigh‐instability‐driven transformation is observed also for viscoelastic materials such as polymers …”
Section: Resultsmentioning
confidence: 97%
“…Compartmentalized micelles self-assemble from pure diblock 21 , triblock 1 , star 8 or comb 22 copolymers. Such structures can also be obtained from the cooperative self-assembly of block copolymer blends, such as AB/B [23][24][25][26] , AB/AC [27][28][29][30] , AB/CB 12,[31][32][33][34][35][36][37] and AB/BAB 38,39 .…”
mentioning
confidence: 99%